For to all those who have, will more be given? Evidence from the adoption of the SELFIE tool for the digital capacity of schools in Spain. (10th May 2022) - Castaño Muñoz, Jonatan; Pokropek, Artur; Weikert García, Lilian
Abstract: This paper explores participation trends in interventions that promote self‐evaluation exercises on the effective use of digital technologies in schools. We use a unique dataset consisting of 83, 185 respondents from 924 Spanish schools that used SELFIE, a tool based on self‐reflection questionnaires that capture different dimensions of school's digital capacity. We benefit from a natural experiment situation caused by the parallel use of SELFIE by two groups of schools. The first group was externally selected as part of a representative sample of Spanish schools. Conversely, the second group voluntarily decided to use SELFIE as a diagnostic tool for a subsequent self‐evaluation exercise. Moreover, a subset of schools were located in regions where authorities embedded SELFIE in broader digitalisation programmes. By comparing these groups, it is shown that schools that decide to participate in SELFIE voluntarily are those with a lower initial digitalisation level. It is also found that the promotion of the use of SELFIE as part of public interventions can increase participation but mainly attracts digitally advanced schools. In conclusion, policy interventions aiming to develop the digital capacity of schools need to plan how to reach those schools that need it more in order to be more equitable. Practitioner notes What is already known about this topic Research has shown the existence of a Matthew effect in the usage of digital technologies in education. The promotion of schools self‐evaluation exercises on digital education is a common policy intervention that is growing in importance. There is a surprising lack of attention to the inequitable effects that programmes aiming to incorporate technologies in educational institutions may generate. What this paper adds This paper investigates the self‐selection trends and (un)equity effects of SELFIE, an EU programme designed to prompt schools' self‐evaluations of digital capacity. When schools decide autonomously, schools with low digital capacity levels tend to participate in SELFIE more. Incorporation of SELFIE into broader public programmes enlarges participation in SELFIE. Incorporation of SELFIE into broader public programmes over‐attracts digitally advanced schools. Implications for practice and/or policy Public policies promoting self‐evaluation exercises on school digital capacity in schools might be a good way for upscaling these exercises. However, these policies should be carefully designed to reduce inequalities and reach these schools that need digitalisation more.